Effective technology to improve the quality of the compressed binary contour image of single-curved Arabic words - على عبدالرحمن عكاشه و مجدى فرج البريكى و على عبدالقادر الشنوكى و محمد نوري حسين (Journal of Pure & Applied Sciences, 2019)
Contour compression (closed curves) is a major challenge in image processing. In this paper, a trapezoidal method will be introduced to compress the boundary of closed single-curved Arabic words. The improved Trapezoid algorithm has been compared with existing methods such as the Ramer algorithm (good quality) and the triangle algorithm (faster) in this work. The Cartesian coordinates of the input contour are processed so that the contour is represented by a set of vertices that selected for the edge of the contour. The measurements in this method are calculated using three criteria based on the mean square error, signal-to-noise ratio and speed. The calculation time of the proposed method is estimated based on the number of performed calculations. The experimental results are obtained in terms of image quality, compression ratio and speed which are encouraging to put forward other points of view. The main advantages of the analyzed algorithm are simplicity and have small numbers of calculations compared to existing algorithms, and they show higher quality than the previous trapezoid algorithm. This method is suitable for the applications where high speed is needed in the real time.